2020
DOI: 10.1007/s10877-020-00537-4
|View full text |Cite
|
Sign up to set email alerts
|

The case for a 3rd generation supraglottic airway device facilitating direct vision placement

Abstract: Although 1st and 2nd generation supraglottic airway devices (SADs) have many desirable features, they are nevertheless inserted in a similar 'blind' way as their 1st generation predecessors. Clinicians mostly still rely entirely on subjective indirect assessments to estimate correct placement which supposedly ensures a tight seal. Malpositioning and potential airway compromise occurs in more than half of placements. Vision-guided insertion can improve placement. In this article we propose the development of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 71 publications
(73 reference statements)
0
39
0
Order By: Relevance
“…All SADs currently have one thing in common: they are inserted blindly, based on an educated guess regarding their correct placement, appropriate size and insertion depth which rely on commonly-used, often-inaccurate indirect assessment and clinical tests [3]. SADs have proved to be forgiving devices despite common non-perfect placement but, occasionally, result in more serious misadventure and poor clinical outcome.…”
Section: Supraglottic Airways Remain Valuable First-line Airway Devices Despite Blind Insertion Resulting In Sub-optimal Positioningmentioning
confidence: 99%
See 3 more Smart Citations
“…All SADs currently have one thing in common: they are inserted blindly, based on an educated guess regarding their correct placement, appropriate size and insertion depth which rely on commonly-used, often-inaccurate indirect assessment and clinical tests [3]. SADs have proved to be forgiving devices despite common non-perfect placement but, occasionally, result in more serious misadventure and poor clinical outcome.…”
Section: Supraglottic Airways Remain Valuable First-line Airway Devices Despite Blind Insertion Resulting In Sub-optimal Positioningmentioning
confidence: 99%
“…Numerous studies have consistently shown that 50-80% of all blindly-inserted 1st and 2nd generation devices SADs (irrespective of type, brand, size and cuffed or non-cuffed design) are placed sub-optimally in the hypopharynx [3,9,10]. There is overwhelming evidence of suboptimal positioning demonstrated by clinical observation [11][12][13], radiographic imaging (CT-scan, MRI, X-rays), fibreoptic studies and ultrasound [14][15][16][17][18][19][20].…”
Section: Supraglottic Airways Remain Valuable First-line Airway Devices Despite Blind Insertion Resulting In Sub-optimal Positioningmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparing the results of insertion of LMA‐Protector ™ and the LMA‐Supreme ™ using the novel vision‐guided (videolaryngoscope) insertion technique, improved incorrect blind insertions from 50% to 80% malpositions to a near optimal (95% correctly positioned SADs) fibreoptic‐controlled position of both devices 24 . The proposed third generation SAD vision‐guided approach, 17 is expected to be a viable and more objective alternative. In the foreseeable future with technological solutions, videolaryngoscopes may be replaced by inbuilt cameras/LEDS, implanted on the SAD wall.…”
Section: Making the Opl Measurement More Objectivementioning
confidence: 99%